2013
DOI: 10.4103/2277-9175.107980
|View full text |Cite
|
Sign up to set email alerts
|

A morphological study to note the variable patterns of cutaneous innervation on the dorsum of foot in south Indian human foetuses and its clinical implications

Abstract: Background:Cutaneous nerves on the dorsum of foot are at risk for iatrogenic damage while performing arthroscopy, local anaesthetic block, surgical approach to the fibula, open reduction and internal fixation of lateral malleolar fractures, application of external fixators, elevation of a fasciocutaneous or fibular flaps for grafting, surgical decompression of neurovascular structures, or miscellaneous surgery on leg, foot and ankle. Hence the present study was undertaken to classify the different patterns of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…Four distinct patterns of innervation was observed by Gupta et al [14]. In 55% of cases, our group I type of innervation was seen (i.e., SN on lateral border of fifth digit, DPN in the first interdigital cleft, rest of the dorsum by SPN).…”
Section: Discussionsupporting
confidence: 55%
“…Four distinct patterns of innervation was observed by Gupta et al [14]. In 55% of cases, our group I type of innervation was seen (i.e., SN on lateral border of fifth digit, DPN in the first interdigital cleft, rest of the dorsum by SPN).…”
Section: Discussionsupporting
confidence: 55%
“…This was observed in two cadavers (10%). Studies by Chandini et al (2012) and Prakash et al (2010) observed the same variation [ 8 , 9 ]. Studies by Madhavi et al (2005) and L.B Soloman et al (2001), observed a similar variation of SN and SPN [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 54%